ANTECEDENTS AND CONSEQUENCES OF MEMORABLE TOURISM EXPERIENCE - Ernawadi, Yadi; Hariyadi Triwahyu Putra (Dinasti International Journal of Management Science, 2020)
The purpose of the research is to examine the role of memorable tourism experience in mediating the impact of destination image on tourist revisit intention. Nowadays, memorable tourism experience needs attention in marketing research area to develop its operational definition related to the specific object such as artificial tourism. The administered questionnaires were used to collect the data from the domestic tourists who were enjoying the resort. Structural equation model has been used to analyze the data and examined the hypotheses. The findings of the research illustrate that memorable tourism experience mediates the influence of destination image toward tourist revisit intention. Based on the limitation of the research, the future research is proposed to widen area of the research in context of tourism industry besides sampling technique related to generalization objective.